MENGENANG PERJUANGAN: GEDUNG JUANG 45 DAN TANTANGAN PELESTARIANNYA DI PEMATANG SIANTAR - Ade Surya Akbar; Steeven Yohannes Hasibuan; Lestari Dara Cinta Utami Ginting (Bajang Institute, 2024)
Gedung Juang 45 Pematang Siantar is a historical building that played an important role in the struggle for Indonesian independence. With its long history, ranging from the colonial period to the physical revolution, this building reflects important changes in the development of the city of Pematang Siantar. Despite its significant historical value, the current condition of the building is concerning and requires special attention for its preservation. In this research, a historical methodology will be used that involves four stages: research of documentary and oral sources, utilization of oral tradition as part of cultural heritage, verification to criticize historical materials, interpretation to combine verified materials, and historiography that involves writing history. Gedung Juang 45 had a multifunctional role in its time, but is currently in a neglected condition and requires conservation efforts. Challenges faced include natural factors, human interference, and lack of institutional support. The existence of Gedung Juang 45 emphasizes the importance of patriotism and sustainable history education. The role of the community in conveying stories through oral tradition is key to enriching local and national history.